PEMODELAN DATA PANEL MENGGUNAKAN RANDOM EFFECT MODEL UNTUK MENGETAHUI FAKTOR YANG MEMPENGARUHI UMUR HARAPAN HIDUP DI INDONESIA - Amin Septianingsih (Jurnal Lebesgue : Jurnal Ilmiah Pendidikan Matematika, Matematika dan Statistika, 2022)
Life Expectancy (UHH) is one indicator of the health status assessment of the population for government programs successful. Life Expectancy at birth is defined as the average estimated length of life of a person that can live from birth. Life Expectancy is affected by the environment, food availability, education, government policy, community’s economy, and so on. In this study, the factors model will be conducted, affects the community’s life expectancy for all Indonesia’s provinces that involve the percentage of household variable which has decent drinking water (AML), percentage of household variable that has decent housing (HL), percentage of household variable that has access to proper sanitation (ASL), percentage of poor residents (PM) variable, and years of schooling average (RLS) variable. The modeling results, three independent variables significantly affected towards life expectancy variable or clean water and sanitation (ASL) variable, poor people (PM) variable, and years of schooling average (RLS) variable. The model result showed that the coefficient determination score is 0,859 which is the independent variable able to explain the dependent variable which is 85,90%, meanwhile the rest is 14,10% which is explained by other variables, outside the model